Business data communications and networking - FitzGerald, Jerry (Wiley, 1996)
Acclaimed for its accuracy, cutting-edge orientation and clarity of presentation, this best-selling text in its new edition is better still. It covers everything MIS professionals need to know about data communications and networks - from hardware and network design to security and LANs.